SARS-CoV-2 specific T-cell immunity in COVID-19 convalescent patients and unexposed controls measured by ex vivo ELISpot assay - Cassaniti, Irene; Percivalle, Elena; Bergami, Federica; Piralla, Antonio; Comolli, Giuditta; Bruno, Raffaele; Vecchia, Marco; Sambo, Margherita; Colaneri, Marta; Zuccaro, Valentina; Benazzo, Marco; Robotti, Carlo; et al. (Clinical microbiology and infection, 2021)
SARS-CoV-2 T-cell response characterization represents a crucial issue for defining the role of immune protection against COVID-19. The aim of the study was to assess the SARS-CoV-2 T-cell response in a cohort of COVID-19 convalescent patients and in a group of unexposed subjects. SARS-CoV-2 T-cell response was quantified from peripheral blood mononuclear cells (PBMCs) of 87 COVID-19 convalescent subjects (range 7–239 days after symptom onset) and 33 unexposed donors by ex vivo ELISpot assay. Follow-up of SARS-CoV-2 T-cell response was performed in ten subjects up to 12 months after symptom onset. The role of SARS-CoV-2 specific CD4 and CD8 T cells was characterized in a group of COVID-19 convalescent subjects. Moreover, neutralizing antibodies were determined in serum samples. In 14/33 (42.4%) unexposed donors and 85/87 (97.7%) COVID-19 convalescent subjects a positive result for at least one SARS-CoV-2 antigen was observed. A positive response was observed up to 12 months after COVID-19 infection (median 246 days after symptom onset; range 118–362 days). Of note, SARS-CoV-2 T-cell response seems to be mainly mediated by CD4 T cells. A weak positive correlation was observed between Spike-specific T-cell response and neutralizing antibody titre (p 0.0028; r2 = 0.2891) and positive SARS-CoV-2 T-cell response was observed in 8/9 (88.9%) COVID-19 convalescent subjects with undetectable SARS-CoV-2 neutralizing antibodies. Cross-reactive SARS-CoV-2 T-cell response in uninfected patients may be due to previous infections with other common coronaviruses. Our data suggest that long-term SARS-CoV-2 T-cell response might accompany a waning humoral response.